Breast ultrasound diagnostic performance and outcomes for mass lesions in Dharma Yadnya general hospital in 2018-2023 - Dana, I. Made Bayu Surya; Atmaja, I. Nyoman Teri (International Journal of Advances in Medicine, 2023)
Background: The latest report by the world health organization and international agency for research on cancer told that the incidence and mortality of breast cancer is the most among female cancer patients. Methods: This is descriptive study which uses medical record of 50 samples patients in Dharma Yadnya general hospital. This study include patients at least 25 years old who presented to the Dharma Yadnya general hospital between January 2019 to March 2023 which get breast ultrasound examination and pathology examination, benign or malignant mass. Results: In ultrasound findings, there are 43 (86%) people with benign cancer, 7 (14%) people with malignant cancer, 43 (86%) people with hipoechoic density and solid lession, 7 (14%) people with isoechoic density and cystic lession, 43 (86%) people with regular margin, 7 (14%) people with irregular margin, 43 (86%) people without lymph nodes axillary, 7 (14%) people with lymph nodes axillary, and by Doppler there are 43 (86%) people without neovascularitation inside lession and 7 (14%) people with neovascularitation inside lession. There are statistically significant relationship (p<0.05) between diagnosis (benign and malignant) with age of patients, density, margin, existence of lymph nodes axillary, and neovascularitation inside the lession by doppler. Conclusions: Breast sonography is the modality of choice for further investigation of palpable breast findings that are not clearly benign and mammographic screen-detected abnormalities.